El aprendizaje cooperativo como estrategia para desarrollar la habilidad de hablar inglés en los estudiantes del primer año de Bachillerato General Unificado de la Unidad Educativa Rumipamba, año lectivo 2016-2017 - Chuquín Cuatis, María Rosa Marlene (2018)
The present work of investigation was focused on the cooperative learning for the first year students of Bachillerato General Unificado (BGU) at “Unidad Educativa Rumipamba”. This document is divided in four chapters which give us a clear explanation about the theme of this project: Chapter one has some bibliographical, scientific and networking information that provides huge elements to gather remarkable information which has been helpful to carry out this project making use of fundamental and notorious concepts from famous authors. Chapter two focuses on providing the methodology, techniques, instruments, to have relevant data and obtain the diagnosis of the current project, as well as to determine the problem that causes the lack of communication skills by the students at Unidad Educativa Rumipamba. Chapter three emphasizes on the cooperative learning and its procedures to be applied to the students with the purpose of having a better understanding about group work and its strengths when applying by the teachers in their English classes. Chapter four takes into account three impacts\; educational, social and ethical. The impacts are remarkable in this project because their consolidation of results has a High Positive impact, which is outstanding and will be granted by the outcome. Finally, conclusions and recommendations are extracted from this investigation with the main object that readers could put into practice the ones mentioned in this work.